Pentingnya Perencanaan Sumber Daya Manusia Dalam Sebuah Organisasi - Violita Grace M; Anna Charlita Lay; Anas Tasya Hastin Hardini; Bunga Astha Rizky (Pusat Riset dan Inovasi Nasional, 2024)
Human resource planning is the first thing an organization or company must do when the company seeks better human resource management. All organizations or companies must determine their future with various different plans following current developments. Currently, changes are occurring quite rapidly, so organizations or companies must be able to keep up with the changes that are occurring quickly and precisely. Organizations or companies must be able to anticipate and adapt to change. Therefore, personnel planning is becoming increasingly important for companies, because the era of globalization, new technologies and organizational change processes overshadow organizational life repeatedly. An organization that is not supported by employees with good quantity, quality, strategy and function, of course the organization will find it difficult to maintain and develop its existence in the future, so that personal planning is successful. Human resource (HR) planning plays a crucial role in organizational success by ensuring the continuity of efficient and effective operations. In the context of globalization and rapid change, HR planning is becoming increasingly important to identify the need for quality and visionary human resources. The unique characteristics of an organization are also a focus in this abstract, where a unique business strategy can become a competitive advantage that is difficult for competitors to imitate. Evaluation of employee performance based on industry principles and the influence of organizational politics as well as a poor evaluation system on employees are also highlighted in this abstract. By understanding the critical challenges facing organizations, including in the context of globalization, HR planning can help organizations to strengthen their position in global competition and face change more adaptively.